Lights Out? The Outlook for Energy in Eastern Europe and Central Asia - World Bank (Washington, DC, 2012)
It is very likely that an energy crunch could hit several countries in Eastern Europe and Central Asia (ECA) in the next five or six years. Before the financial crisis of 2008, several electricity importing countries in the region had begun to experience difficulties with supply; however, the crisis has reduced demand and created some breathing room. It has also created a window of opportunity to take action to mitigate the impact of the anticipated energy crunch. But countries need to act now. Mitigating actions are required on both the supply side and the demand side and will require significant investments (about $3.3 trillion in 2008 dollars over the next 20 years, or about 3% of cumulative gross domestic product) if the region wants to meet all its anticipated energy needs. This level of investment cannot be provided by the public sector alone and measures will be required to create a climate that appeals to private sector investors. In conclusion, the region faces a potential energy crunch. The financial crisis has provided some breathing room to address the potential energy constraints, but countries need to act quickly to take advantage of this window of opportunity by promoting an attractive climate for investment. At the same time they need to ensure that the energy strategies they pursue are perceived as being responsive to environmental concerns.